1980
DOI: 10.1111/j.1526-4610.1980.hed2001013.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Antagonists in Migraine Prophylaxis A Clinical Trial Using Aspirin and Dipyridamole

Abstract: SYNOPSIS The platelet hyperaggregability of the migraine population has lead us to postulate that platelet antagonists might be effective in migraine prophylaxis. A double‐blind cross‐over study of aspirin, 325 mg BID, combined with dipyridamole, 25 mg TID, compared to placebo and pretreatment conditions was undertaken. Platelet aggregation studies were done during the three month active medication and placebo periods. In patients with platelet hyperaggregability significant improvement occurred in headache fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…There is now substantial evidence to support a prophylactic role for low dosages of aspirin in the prevention of migraine (Baldrati et al 1983;Buring et al 1990;Masel et al 1980;O'Neill & Mann 1978;Ryan & Ryan 1982). This effect is probably mediated at least in part by the anti platelet effects of aspirin described previously.…”
Section: Migrainementioning
confidence: 95%
“…There is now substantial evidence to support a prophylactic role for low dosages of aspirin in the prevention of migraine (Baldrati et al 1983;Buring et al 1990;Masel et al 1980;O'Neill & Mann 1978;Ryan & Ryan 1982). This effect is probably mediated at least in part by the anti platelet effects of aspirin described previously.…”
Section: Migrainementioning
confidence: 95%
“…135 Results of other trials suggest that dipyridamole alone or in combination with aspirin has a beneficial effect for migraine prophylaxis; however, failure to use appropriate control groups and statistical evaluation diminishes their value. [136][137][138] PERIPHERAL CIRCULATION DISORDERS Platelets are involved early in the formation of thrombi in venous circulation, although fibrin is the major component.9 The efficacy of low-dose heparin to prevent postoperative deep vein thrombosis (DVT) has been demonstrated. 139 Since heparin at low concentrations may affect platelet function primarily, it has been postulated that anti platelet agents also may be useful to prevent DVT.…”
Section: Drug Intelligence and Clinical Pharmacy 1984 Nov Vol 18 873mentioning
confidence: 99%
“…Benseñor et al 19 was the only study that described incapacitation as an outcome; after having restricted the analysis to women who fulfilled the modified IHS criteria for migraine, they reported that there was a significant improvement in incapacitation after 12 months (OR = 1.45; 95% CI = 1.04 -2.02). Masel et al 30 reported on an intervention combining dipyridamole and aspirin, while Bousser et al 25 combined dihydroergotamine with aspirin as an active prophylactic treatment. Each study reported different doses of aspirin, and both compared the outcomes with those of a placebo group.…”
Section: The Effectiveness Of Aspirin For Prophylaxis Of Migrainementioning
confidence: 99%
“…28 Only one study 19 classified migraine according to the IHS criteria. 29 Other studies either used their own definition of migraine 30 or did not mention at all how migraine was defined. 17,21,24 Overall, the studies 100,000 men in one year".…”
Section: Study Characteristicsmentioning
confidence: 99%